STRUKTUR KONEKSI MATEMATIS SISWA KELAS X PADA MATERI SISTEM PERSAMAAN LINIER DUA VARIABEL - Melinda Rismawati; Edy Bambang Irawan; Hery Susanto (Graduate School of Universitas Negeri Malang, 2017)
Mathematical connection is an interconnection among concepts in a similar topic and an interconnection among materials in a particular topic with other topic in mathematics. When students can connect mathematical ideas, their understanding is deeper and more lasting. This research studies about the structure of mathematical connection of the students with a high mathematical abilities in solving problem on Linear Equation System Two Variable (LESTV) by giving individual worksheet and interviewing one subject with a high mathematical abilities. The structure of mathematical connection is studied by linking the indicators of mathematical connection that are: (1) recognizing and utilizing the relationship between mathematical ideas, and (2) understanding how the mathematical ideas are connected and built each other resulting the ideas thoroughly and coherently.Koneksi matematis adalah hubungan antar konsep dalam satu topik yang sama, serta hubungan antar materi dalam matematika. Jika siswa dapat membuat banyak koneksi matematis, maka pembelajaran akan bermakna dan optimal. Penelitian ini mengkaji struktur koneksi matematis siswa berkemampuan matematis tinggi dalam menyelesaikan soal SPLDV dengan memberikan lembar tugas individu dan melakukan wawancara kepada satu subjek yang memiliki kemampuan matematis tinggi. Hasil tes dianalisis menggunakan indikator koneksi matematis (1) mengenal dan menggunakan hubungan diantara ide-ide matematis, (2) memahami bagaimana ide matematis saling berhubungan dan membangun satu sama lain untuk menghasilkan keseluruhan yang koheren.